2017
DOI: 10.1002/gcc.22519
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence supporting a metastasis suppressor role for Stard13 (Dlc2) in ErbB2 (Neu) oncogene induced mouse mammary tumors

Abstract: Overexpression of dominant oncogenes and the loss of tumor suppressor genes are basic genetic events in the acquisition of the malignant phenotype. The erb-b2 receptor tyrosine kinase 2 (ERBB-2) proto-oncogene is overexpressed in 20-30% of human breast cancers. The StAR related lipid transfer domain containing 13 gene (STARD13), also known as Deleted in Liver Cancer-2 (DLC-2), maps to chromosome band 13q12.3 and is frequently downregulated in human cancers, including 72% of breast cancers. It encodes a RhoGAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
(65 reference statements)
1
6
2
Order By: Relevance
“…The StarD13 gene as a target of miR-720 could regulate the abilities of cell growth, migration and invasion in colorectal cancer [28]. Earlier in vivo mice experiments showed that StarD13 was a metastasis suppressor gene, which is consistent with our results [29].…”
Section: Discussionsupporting
confidence: 90%
“…The StarD13 gene as a target of miR-720 could regulate the abilities of cell growth, migration and invasion in colorectal cancer [28]. Earlier in vivo mice experiments showed that StarD13 was a metastasis suppressor gene, which is consistent with our results [29].…”
Section: Discussionsupporting
confidence: 90%
“…23 Interesting results were also presented in a work of Basak et al ., where authors showed that in the mammary cancer model the DLC2 deletion did not change the tumor growth, however it had an impact on the metastasis formation, which suggests its metastasis suppressor rather than tumor suppressor role. 24 Our results did not confirm the DLC2 deficiency as a common feature of HCC at the protein and gene levels in our experimental group. Similar results were presented in the work of Wang et al ., where authors showed that the major member of the DLC family whose expression is reduced in HCC is DLC1, while the expression of DLC2 was not diminished and even was increased in the subset of tumors.…”
Section: Discussioncontrasting
confidence: 78%
“…Furthermore, recent findings have revealed that StarD13 and its competing endogenous RNA, ceRNAs-3’UTRs inhibit breast cancer metastasis by inhibiting epithelial to mesenchymal transition (EMT) [ 65 67 ]. A homozygote or heterozygote loss of StarD13 in mammary tumors linked to ErbB2 (tyrosine phosphate -receptor), increased lung metastasis in vivo as well [ 68 ], further demonstrating StarD13 invasion and metastasis suppressor functions.…”
Section: Discussionmentioning
confidence: 99%